1991
DOI: 10.1159/000186476
|View full text |Cite
|
Sign up to set email alerts
|

Captopril but Not Acebutolol, Prazosin or Indomethacin Decreases Postexercise Proteinuria

Abstract: Strenuous physical exercise causes transient proteinuria and renal hemodynamic changes: decrease of renal blood flow and to a lesser extent of the glomerular filtration rate, and an increase of the filtration fraction. However, the mechanisms of these modifications are still poorly understood. In order to elucidate them we performed maximal exercise tests on 8 untrained healthy volunteers after inhibition of the renin-angiotensin system (RAS) by captopril, the sympathetic nervous system by a β-blocking drug (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Angiotensin II, another possible effective vasoconstrictor agent in renal hemodynamics, has been investigated extensively. Angiotensin II production after renin release has been shown to cause an increase in transglomerular pressure and filtration fraction via a more prominent constriction of efferent arteriole (3,6). On the other hand, some authors did not observe an involvement of renin-angiotensin system in postexercise proteinuria (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin II, another possible effective vasoconstrictor agent in renal hemodynamics, has been investigated extensively. Angiotensin II production after renin release has been shown to cause an increase in transglomerular pressure and filtration fraction via a more prominent constriction of efferent arteriole (3,6). On the other hand, some authors did not observe an involvement of renin-angiotensin system in postexercise proteinuria (24).…”
Section: Discussionmentioning
confidence: 99%
“…It is described as a "temporary increase in protein excretion by urine in healthy individuals after exercise" (27) and was shown to occur in various exercising laboratory animals as well as in humans (5,14,27). The basic mechanisms of postexcercise proteinuria are increased glomerular permeability and/or exceeding the maximum tubular reabsorption capacity for proteins (6,29). The permeability of the glomerular capillary membrane, which does not allow the filtration of macromolecules under normal circumstances, increases because of the renal hemodynamic alterations occurring during exercise.…”
mentioning
confidence: 99%
“…Previous studies have shown ACE inhibition might prevent post-exercise proteinuria [4, 5, 7, 10]. However, ACE inhibition also induces a rise in plasma bradykinin levels as the kininase activity is blocked as well [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased activity of renal sympathetic nerves, an increase in circulating adrenaline levels also leads to cumulative vasoconstriction in the nephrons’ afferent and efferent arterioles [3]. Increased sympathetic nerve activation during exercise also induces renin release [4, 5], increasing angiotensin II (Ang II), which is a potent vasoconstrictor and has important implication for renal haemodynamics. The FF increases especially due to the vasoconstriction of the efferent arteriole [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation